The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0047834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mitochondrial Genomics within and among Yeast Species of the Lachancea Genus

Abstract: Yeasts are leading model organisms for mitochondrial genome studies. The explosion of complete sequence of yeast mitochondrial (mt) genomes revealed a wide diversity of organization and structure between species. Recently, genome-wide polymorphism survey on the mt genome of isolates of a single species, Lachancea kluyveri, was also performed. To compare the mitochondrial genome evolution at two hierarchical levels: within and among closely related species, we focused on five species of the Lachancea genus, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…In L. kluyveri , a recent study found evidence for mobility of both cox1 and cob introns, noting presence/absence polymorphisms for three out of four cob and three out of five cox1 introns (Jung et al 2012). In line with widespread mobility in this species, all introns with the exception of the first cob intron encode endonucleases (Friedrich et al 2012). As predicted under a model where gene identity is secondary but mobility plays a pivotal role in nonrandom nucleotide diversity at intron–exon boundaries, we observe SNP density gradients across both cob (τ = −0.21, P = 0.03, Figure 2D) and cox1 exons (τ = −0.29, P = 0.002) in L. kluyveri , whereas in S. pombe a negative SNP gradient is evident for cob (τ = −0.31, P = 0.002) but not cox1 (τ = 0.16, P = 0.1).…”
Section: Resultsmentioning
confidence: 86%
“…In L. kluyveri , a recent study found evidence for mobility of both cox1 and cob introns, noting presence/absence polymorphisms for three out of four cob and three out of five cox1 introns (Jung et al 2012). In line with widespread mobility in this species, all introns with the exception of the first cob intron encode endonucleases (Friedrich et al 2012). As predicted under a model where gene identity is secondary but mobility plays a pivotal role in nonrandom nucleotide diversity at intron–exon boundaries, we observe SNP density gradients across both cob (τ = −0.21, P = 0.03, Figure 2D) and cox1 exons (τ = −0.29, P = 0.002) in L. kluyveri , whereas in S. pombe a negative SNP gradient is evident for cob (τ = −0.31, P = 0.002) but not cox1 (τ = 0.16, P = 0.1).…”
Section: Resultsmentioning
confidence: 86%
“…Few population genetic investigations on intraspecific mtDNAs in yeasts exist [4547], and none for Saccharomyces species. To provide a window onto recent evolutionary changes in the mtDNA, we compared the intraspecific genetic variation in mitochondrial genomes from 100 strains of S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report suggested that the alteration of the gene order within yeast genera could be related to the mitochondrial genome size (Sulo et al 2017). While the Lachancea and Yarrowia clades, with mitochondrial genome less than 50 kb, show high synteny across species (Friedrich et al 2012;Gaillardin et al 2012), the Saccharomyces clade (mitochondrial genome size > 65 kb) is more prone to rearrangements (Sulo et al 2017). Indeed structural rearrangements were also detected in the mitochondrial genome of S. paradoxus (Yue et al 2017).…”
Section: Structural Rearrangements Are Rare In Mitochondrial Genomesmentioning
confidence: 99%